Conjugal violence - Nunes, Amália Silva (2003)
Domestic violence can be defined as violence that occurs in an intimate relationship, exerted by one partner over the other in order to control and dominate the. Arises in the context of current or past relationships, straight or gay; develops in most cases in heterosexual relations and the female victim. It is a complex social problem, with important consequences for the health of the victims. This synthesis work aims to provide some information about the reality of domestic violence - concept, types of violence, epidemiology, impact on the health of victims - and point suggestions for action medical presence in this form of violence, primary prevention and detection and monitoring of situations. A review of publications - articles for medical journals, publications of organizations with work in this area, books and material available on the internet - for the period from 1997 to 2002. The work also includes discussion of the findings of a group of health professionals and organizations adept at working with this issue in the integrated project of the European Community Daphe